Brood thermoregulation effectiveness is positively linked to the amount of brood but not to the number of bees in honeybee colonies - Godeau, Ugoline; Pioz, Maryline; Martin, Olivier; Rüger, Charlotte; Crauser, Didier; Le Conte, Yves; Henry, Mickael; Alaux, Cédric (Peer Community Journal)

(untitled)
To ensure the optimal development of brood, a honeybee colony needs to regulate its temperature within a certain range of values (thermoregulation), regardless of environmental changes in biotic and abiotic factors. While the set of behavioural and physiological responses implemented by honeybees to regulate the brood temperature has been well studied, less is known about the factors that may influence the effectiveness of this thermoregulation. Based on the response threshold model of task allocation, increased effectiveness of colony homeostasis should be driven by increases in group size. Therefore, we determined whether colony size (number of adult bees and amount of brood) positively influenced the effectiveness of brood thermoregulation that we measured via two criteria: (i) the brood temperature accuracy, via mean brood temperature, supposedly close to the optimum value for brood rearing, and (ii) the stability of the temperature around the mean value. Finally, within the applied perspective of honeybee colony monitoring, we assessed whether the effectiveness of thermoregulation could be used as a proxy of colony size. For that purpose, we followed 29 honeybee colonies over two years, measured both brood and adult population size regularly over the beekeeping season, and monitored the brood temperature over the 24 hours preceding the inspections of these colonies. We then studied the effect of the size of the colony (number of adult bees and number of brood cells), as well as meteorological variables, on the effectiveness of thermoregulation (mean and stability of brood temperature). We found a clear link between meteorological conditions and brood thermoregulation (mean temperature and its stability). Interestingly, mean brood temperature was also positively linked to the amount of brood, while its stability did not seem influenced by the size of the colony (number of bees or brood amount). The relationship between brood amount and mean temperature was however too weak for clearly discriminating colony population size based solely on the brood thermoregulatory effectiveness. These results demonstrate an extremely high effectiveness of honeybee colonies to thermoregulate the brood regardless of colony size.